Human resources management in large information-based services companies: towards a common framework?. (31st March 2005) - Viardot, Eric
Professional information based services are the fastest growing activities in the high technology information sector. But the management of those companies is a largely unexplored area of strategic management. This paper reports the findings of an exploratory survey of the ten largest international companies in this field about their models and practice of people management. The paper underlines the strategic importance of HR management for those companies whose people are their most important assets and who have recently experienced meteoric growth in the number of their employees. Findings suggest that there is a common framework of practices which can be divided in seven different components. These include a vision of the role of the employees, as well as their recruitment, training, evolution, management, communication, and remuneration. The paper presents and discusses the impact of the service technology on each of those components.